ETUDE ET SIMULATION DES MICROSYSTEMES A BASE DE LA TECHNOLOGIE MEMS - BOUDJELLA SABRIA (My University, 2014)
Our work is oriented in the context of research on microsystems MEMS meaning: systems Micro-Electro-Mechanical Systems. A microsystem is primarily a small system including sensors, actuators and electronics designed to provide a number of functions, such as perception of the environment (sensor), analysis and processing of data, decision, communication with the outside world, or to an action on the environment itself. RF MEMS microsystems are dedicated to RF applications. Our work is based on the study and simulation of two examples very useful and answered Microsystems RF MEMS: Switches and bandpass filters. In the first part, we are interested in modeling geometric structures. This is an important step in the design (including the design of the structure), as it allows to predict ii the electrical behavior of microstructures at high frequencies. We use both square and circular structures and present the effect of the deflection depending on the variation of the thickness of the switch itself. Determining the rate of deflection is a function of the dimensions of the plates forming capacity reconfigurable switches, and plays an important role in the specification of values of the capacitances between the beams (Cmin, Cmax). For use as RF MEMS bandpass filter model, it was noted that the change in deflection select maximum and minimum value for a specific width between beams micro-switches (2 states: On / Off), so this filter has two operating frequency when the micro-switches are high or low state, thus limiting a frequency band. Thus, the modes of operation of RF MEMS are based on the bending mode of the inserted micro-switches that are the elements and must be described precisely on the mechanical and electronic physical plans.